Analisis Kesenjangan Antara Materi IPS Dan Realitas Kehidupan Sosial Siswa Di SMA Negeri 8 Seluma - Edo Setiawan; Mus Mulyadi; Ahmad Walid; Rosi Delta Fitriana (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This study analyzes the gap between Social Studies (IPS) learning materials and the social realities experienced by students at SMA Negeri 8 Seluma. Social Studies learning in senior high schools is designed to develop students’ social awareness, critical thinking, and understanding of social life within society. However, in practice, IPS learning often emphasizes theoretical understanding rather than contextual experiences closely related to students’ daily social environments. This research employed a qualitative descriptive approach with data collected through observation, in-depth interviews, and documentation. The informants consisted of IPS teachers and students selected through purposive sampling. The findings indicate that there is a significant gap between IPS materials taught in the classroom and the actual social realities faced by students. The learning process tends to be teacher-centered, theoretical, and focused on memorization, while contextual learning based on real social phenomena remains limited. Students experience difficulties in relating concepts such as social interaction, economic activities, and social change to their daily lives. This condition is influenced by the limited use of contextual examples and the minimal integration of local social issues into lesson planning. The study concludes that IPS learning should adopt a more contextual and student-centered approach in order to improve students’ social understanding and enhance the relevance of learning to real-life conditions.